Design and implementation of MRP system in SMEs - Rivera Poma, Juan Manuel (2014)
This article addresses the issue of Material Requirements Planning (MRP) and its importance as an administrative system planning and management of the materials required for the production processes of a company. The objective of this research is to present proper procedures and recommendations for the implementation of MRP in SMEs through simplified explanations for successful implementation. Finally, the benefits obtained in a particular case and conclude that the MRP, when properly used are presented, provides a solution for SMEs in areas such as minimizing inventory costs and supply at the required time.